2018
DOI: 10.3992/1943-4618.13.2.20
|View full text |Cite
|
Sign up to set email alerts
|

Durability Performance and Dimensional Stability of Polypropylene Fiber Reinforced Concrete

Abstract: In this study, the durability performance and dimensional stability of polypropylene fiber reinforced concrete mixture were investigated. For this purpose, two series of concrete mixtures, including a 0.45 water/cement ratio was prepared both in the absence and presence of fiber. A CEMI 42.5 R type portland cement and crushed limestone aggregate with a maximum particle size of 25 mm were used. In addition to the control mixture without fiber, three different concrete mixtures were prepared by adding polypropyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…is is mainly because a part of expansion stress of gypsum and AFT in pores is consumed by the tensile stress of polypropylene fiber, which makes CI30P0.1 not crack easily. is is basically consistent with the research results of Mardani-Aghabaglou et al [44], who have found that by adding polypropylene fiber as 0.8% of total volume into the concrete, there were significant differences in expansion especially after 60 days, and the expansion value of this mixture was determined to be approximately 25% lower than that of the control Advances in Materials Science and Engineering mixture. So, the amount of sulfate ion diffusing into CI30P0.1 will be limited, which restricts the expansive gypsum and AFT to generate in concrete pores.…”
Section: E Results Of Expansion Variationsupporting
confidence: 92%
See 2 more Smart Citations
“…is is mainly because a part of expansion stress of gypsum and AFT in pores is consumed by the tensile stress of polypropylene fiber, which makes CI30P0.1 not crack easily. is is basically consistent with the research results of Mardani-Aghabaglou et al [44], who have found that by adding polypropylene fiber as 0.8% of total volume into the concrete, there were significant differences in expansion especially after 60 days, and the expansion value of this mixture was determined to be approximately 25% lower than that of the control Advances in Materials Science and Engineering mixture. So, the amount of sulfate ion diffusing into CI30P0.1 will be limited, which restricts the expansive gypsum and AFT to generate in concrete pores.…”
Section: E Results Of Expansion Variationsupporting
confidence: 92%
“…In addition, it is known that the expansions variation rate of CI30P0.1 and CI30P0 is basically increasing from 0 to 56 days, which indicates that the expansive gypsum and AFT is forming in CI30P0.1 and CI30P0, and the polypropylene fibers do not play the role inhibiting the expansion of CI30P0.1 at this time. Mardani-Aghabaglou et al [44] obtained the similar experimental result; that is, within the first 30 days after production, the expansion values of all specimens were close to each other.…”
Section: E Results Of Expansion Variationsupporting
confidence: 66%
See 1 more Smart Citation
“…This event is thought to be due to the increase in the pore rate in the matrix due to the use of fiber. Similar statements were reported by other researchers 44,45 . An indicator of this is the decrease in compressive strength with the increase in fiber usage rate.…”
Section: Resultssupporting
confidence: 89%
“…It was noticed that the mixtures containing 0.8% of polypropylene fibers exhibited a perfect resistance against 300 cycles of freezing and thawing, and above this volume the resistance was adversely impacted compared to the conventional mixture. Thereby, the entry of water to the capillary pores deteriorates the pore structure with inner extension through freezing(Mardani-Aghabaglou et al 2018). Nguyen et al found that 2% of polypropylene fibers fulfilled a crucial performance in improving the durability of the high performance fiber reinforced cementitious composites after exposure to 180 cycles of freezing and thawing.…”
mentioning
confidence: 99%